Phosphodiesterase inhibitors in clinical urology. Issue 3 (May 2013) - Ückert, Stefan; Kuczyk, Markus A; Oelke, Matthias
To date, benign diseases of the male and female lower urinary and genital tract, such as erectile dysfunction, bladder overactivity, lower urinary tract symptomatology secondary to benign prostatic hyperplasia and symptoms of female sexual dysfunction (including arousal and orgasmic disorders), can be therapeutically approached by influencing the function of the smooth musculature of the respective tissues. The use of isoenzyme-selective phosphodiesterase (PDE) inhibitors is considered a great opportunity to treat various diseases of the human urogenital tract. PDE inhibitors, in particular the PDE5 (cyclic GMP PDE) inhibitors avanafil, lodenafil, sildenafil, tadalafil, udenafil and vardenafil, are regarded as efficacious, having a fast onset of drug action and an improved effect-to-adverse event ratio, combining a high response rate with the advantage of an on-demand intake. The purpose of this review is to summarize recent as well as potential future indications, namely, erectile dysfunction, Peyronie's disease, overactive bladder, urinary stone disease, lower urinary tract symptomatology secondary to benign prostatic hyperplasia and premature ejaculation, for the use of PDE inhibitors in clinical urology.